Benin : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2008)
The strategy adopted by Benin to strengthen its macroeconomic stability and promote private-investment-led growth has been detailed in the note. The statistical data on gross domestic product by sector of origin at current prices and at constant supply, production and producer prices of cotton, products, production, and cultivated area of principal food crops in Benin has been given. The retail price of major petroleum products, consumer price index in urban areas, industrial minimum legal wage, central government revenue and expenditure, and related statistical information is detailed.